SME PERFORMANCE MEASUREMENT STRATEGY (LITERATURE STUDY REVIEW AND FUTURE RESEARCH DIRECTION) - Susilawati, Susilawati (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Performance measurement is the process by which the organization sets the parameters of the results to be achieved by programs, investments, and acquisitions made. The performance measurement process always requires realistic evidence to determine the level of progress of an organization in achieving its goals. This study aims to explain the measurement of strategy oreantation in more depth. A qualitative approach was used in this research, by applying library research methods. The data used is in the form of secondary data, namely scientific articles with the source of the data used is electronic data sourced from Emerald Insight, Sciencedirect, Google Scholar to SAGE. The results obtained are measurement of strategy orientation that is suitable for SMEs, namely Customer, Competitor, Low cost orientation, Entrepreneurship and Innovation. But in general, strategy orientation can be grouped into three main elements, namely: first market orientation, which consists of knowledge, competencies and skills of employees to build good relationships with consumers, second technology orientation which includes understanding employees and managers in the use of new technology, and the last is Orientation to reduce the cost includes the tendency to reduce costs in the form of cost leadership strategies so as to increase market share. These three elements can interact dynamically and continuously so that it will produce a competitive advantage.